Impact of Different H/D Ratio on Axial Gas Holdup Measured by Four-Tips Optical Fiber Probe in Slurry Bubble Column (Journal of Engineering, 2016)
In wide range of chemical, petrochemical and energy processes, it is not possible to manage without slurry bubble column reactors. In this investigation, time average local gas holdup was recorded for three different height to diameter (H/D) ratios 3, 4 and 5 in 18" diameter slurry bubble column. Air-water-glass beads system was used with superficial velocity up to 0.24 m/s. the gas holdup was measured using 4-tips optical fiber probe technique. The results show that the axial gas holdup increases almost linearly with the superficial gas velocity in 0.08 m/s and levels off with a further increase of velocity. A comparison of the present data with those reported for other slurry bubble column having diameters larger than 18" and H/D higher than 5 indicated that there is little effect of diameter on gas holdup. Also, local section-average gas holdups increase with increasing superficial gas velocity, while the effect of solid loading are less significant than that of superficial gas velocity.